2000
DOI: 10.1086/309410
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Abundances in the Atmosphere of the T Dwarf Gl 229B

Abstract: We present new, high resolution, infrared spectra of the T dwarf Gliese 229B in the J, H, and K bandpasses. We analyze each of these as well as previously published spectra to determine its metallicity and the abundances of NH3 and CO in terms of the surface gravity of Gl 229B, which remains poorly constrained. The metallicity increases with increasing gravity and is below the solar value unless Gl 229B is a high-gravity brown dwarf with log g(cgs) ~ 5.5. The NH3 abundance is determined from both the H and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
219
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(233 citation statements)
references
References 37 publications
13
219
1
Order By: Relevance
“…As a result, the peak-to-trough variation in emitted Ñux is again somewhat smaller for the cloudy model. We note that clear atmosphere models for T dwarfs such as Gl 229B and GD 165B typically overpredict the water band depths (e.g., Marley et al 1996 ;Allard et al 1996 ;Tsuji et al 1996 ;Saumon et al 2000 ;Geballe et al 2001) and suggest that the attenuation of Ñux by the top of the silicate cloud deck may be responsible for this e †ect. Notably, these model atmospheres illustrate the origin of the curious change in infrared colors of the L and T dwarfs (e.g., Kirkpatrick et al 1999 ;Fan et al Mart•n 2000).…”
Section: Ertical Cloud Structurementioning
confidence: 70%
“…As a result, the peak-to-trough variation in emitted Ñux is again somewhat smaller for the cloudy model. We note that clear atmosphere models for T dwarfs such as Gl 229B and GD 165B typically overpredict the water band depths (e.g., Marley et al 1996 ;Allard et al 1996 ;Tsuji et al 1996 ;Saumon et al 2000 ;Geballe et al 2001) and suggest that the attenuation of Ñux by the top of the silicate cloud deck may be responsible for this e †ect. Notably, these model atmospheres illustrate the origin of the curious change in infrared colors of the L and T dwarfs (e.g., Kirkpatrick et al 1999 ;Fan et al Mart•n 2000).…”
Section: Ertical Cloud Structurementioning
confidence: 70%
“…tion is important when we consider the difficulty in estimating e †ective temperature from spectral data. These objects are clearly not blackbodies, and brightness temperatures derived from spectral data can range over 1000 K in the 1È2.5 km regime (Saumon et al 2000). However, a reasonable estimate of can be obtained if the total luminosity T eff of a degenerate brown dwarf is known.…”
Section: E †Ective T Emperaturesmentioning
confidence: 99%
“…These scales Mart•n clearly bracket the e †ective temperatures calculated here TABLE 17 Leggett et al (2001) are T eff indicated by triangles. The two Ðlled circles plot estimates for Gliese T eff 229B (Saumon et al 2000) and Gliese 570D (Burgasser et al 2000a ;Geballe et al 2001). Spectral type/e †ective temperature scales from Kirkpatrick et al (1999Kirkpatrick et al ( , 2000 and Basri et al (2000) are indicated, with the latter scale corrected to the Kirkpatrick et al (1999) spectral sequence.…”
Section: T He T Emperatures Of L Dwarfsmentioning
confidence: 99%
“…Burrows et al (2001) presented a review of the substantial subsequent work devoted to understanding the properties of L and T dwarfs. Although the comparison of models to the spectra of individual objects such as Gl 229B (Saumon et al 2000) and Gl 570D (Geballe et al 2001;Saumon et al 2006) has played an important role in the progression of the field, relatively little work has been done on comparing entire classes of models to uniform data sets (see, however, Burgasser et al 2006a). Such comparisons are important, as they can reveal the global properties of a set of objects and highlight the systematic strengths and weaknesses of the models.…”
Section: Introductionmentioning
confidence: 99%